Response Curves for Ammonia and Methane Emissions From Stored Liquid Manure Receiving Low Rates of Sulfuric Acid - Sokolov, Vera; Habtewold, Jemaneh; VanderZaag, Andrew; Dunfield, Kari; Gregorich, Edward; Wagner-Riddle, Claudia; Venkiteswaran, Jason J.; Gordon, Robert (Frontiers in Sustainable Food Systems, 2021)
Addition of sulfuric acid (H2SO4) to liquid dairy manure (slurry) reduces methane (CH4), nitrous oxide (N2O), and ammonia (NH3) emissions. There is interest in understanding how gaseous emissions respond to decreasing rates of acidification, to determine economically optimum application rates. Acidification rates were tested ranging from 0 to 2 g sulfuric acid (H2SO4) L−1 slurry in six meso-scale outdoor storage tanks, each filled with 10.6 m3 slurry and stored for 114 d. Results showed that the rate of acidification for maximum inhibition of CH4 and NH3 emissions varied markedly, whereas N2O reductions were modest. Reductions of CH4 increased with acid rate from 0 to 1.2 g L−1, with no additional response beyond >1.2 g L−1. In contrast to CH4, inhibitions of NH3 showed a linear response across all rates, although reductions were ≤ 30%. Thus, higher acidification rates would be required to achieve greater NH3 emission reductions. Our findings indicate that achieving >85% NH3 emissions reductions would require 4 × more acid than achieving >85% CH4 reductions. Decisions on optimum H2SO4 rates will depend on the need to mitigate CH4 emissions (the primary greenhouse gas emitted from stored liquid manure) or reduce NH3 emissions (which is regulated in some regions). These results will help develop guidelines related to the potential costs and benefits of reducing emissions through acidification.